2007
DOI: 10.3390/i8080842
|View full text |Cite
|
Sign up to set email alerts
|

A Spectral-SAR Model for the Anionic-Cationic Interaction in Ionic Liquids: Application to Vibrio fischeri Ecotoxicity

Abstract: Within the recently launched the spectral-structure activity relationship (S-SAR)analysis, the vectorial anionic-cationic model of a generic ionic liquid is proposed, alongwith the associated algebraic correlation factor in terms of the measured and predictedactivity norms. The reliability of the present scheme is tested by assessing the Hanschfactors, i.e. lipophylicity, polarizability and total energy, to predict the ecotoxicityendpoints of wide types of ionic liquids with ammonium, pyridinium, phosphonium,c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
33
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(33 citation statements)
references
References 43 publications
0
33
0
Order By: Relevance
“…The first model is based on the vectorial summation of the produced anionic and cationic biological effects. In other words, this so-called |1+> model is constructed from the superposition of the anionic (subscripted with A) and cationic (subscripted with C) activities, and can be formally represented as [27,30]:…”
Section: From In Cerebro To In Silico Principles Of Ecotoxicitymentioning
confidence: 99%
See 2 more Smart Citations
“…The first model is based on the vectorial summation of the produced anionic and cationic biological effects. In other words, this so-called |1+> model is constructed from the superposition of the anionic (subscripted with A) and cationic (subscripted with C) activities, and can be formally represented as [27,30]:…”
Section: From In Cerebro To In Silico Principles Of Ecotoxicitymentioning
confidence: 99%
“…The next step in the ecotoxicological evaluation of the synthetized mesoporous silica is to use the logistic enzyme kinetic and Spectral-SAR methods [26][27][28][29][30] with acetylcholine esterase as a working enzyme. Acetylcholine is a notably good marker for monitoring the evolution in ionic liquids, due to the similar chemical structures of many ionic liquids cations and acetylcholine and especially because this enzyme does not follow the standard Michaelis-Menten kinetics mechanism.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The quaternary imidazolium compounds have good antielectrostatic properties and they are used in cosmetic, textile and pharmaceutical industries [8]. The broad spectrum of antimicrobial activity, low toxicity, good stability, lack of odour of usable solutions cause those compounds to be widely used as disinfectant and cleaning agents in food and pharmaceutical industries and in hospitals [15,16]. Numerous tests indicated that antimicrobial properties of bisquaternary imidazolium chlorides depend on their structure (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…QSAR, which quantitatively correlates the variations in biological activity with the properties or molecular structures, is one of the most effective approaches for designing new chemical identities and understanding the action mechanisms of drugs [14,15]. In order to establish the QSAR model, suitable statistical methods are applied to establish correlations between chemical structures and their biological activities, such as Multiple Linear Regression (MLR), Principal Component Analysis (PCA), Partial Least Squares (PLS), artificial neural networks (ANN), Spectral-SAR Algorithm [16,17], and so on. When a model is established, the findings can be used to predict the properties of new compounds and see which structural factors influence those properties.…”
Section: Introductionmentioning
confidence: 99%